The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
15th AIAA Aviation Technology, Integration, and Operations Conference 2015
DOI: 10.2514/6.2015-2737
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo based Robust MDO applied to Aircraft Conceptual Design: a technical-financial coupling optimization strategy

Abstract: Aircraft Conceptual Design is a challenging task that requires not only the understanding of many different disciplines, but also how they interact with each other, leading to many trade-off analyses. The complexity of these interactions grows fast with the number of variables, disciplines and goals of the problem. Multidisciplinary Analysis and Optimization tools can be very helpful to explore the design space, but it is up to the engineering team to define the objective function: optimal with respect to what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Where Price is obtained from Figure 2 and the Market Share can be estimated using the Benefit Index (BI) and Attractiveness Index (AI) defined in reference [11]. The benefit index is a functional intended to measure the perceived value of a collection of performance attributes from the customers point of view.…”
Section: Aircraft Unit Price Versus Productivity Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…Where Price is obtained from Figure 2 and the Market Share can be estimated using the Benefit Index (BI) and Attractiveness Index (AI) defined in reference [11]. The benefit index is a functional intended to measure the perceived value of a collection of performance attributes from the customers point of view.…”
Section: Aircraft Unit Price Versus Productivity Indexmentioning
confidence: 99%
“…: how much of the market forecast the design would be able to capture. In reference [11] a Market Share model based on Personas b methodology 22 was proposed and employed in order to compare optimized designs for the traditional strategy (i.e. min{MTOW}) and the technical-financial coupled strategy (i.e.…”
Section: Aircraft Unit Price Versus Productivity Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, it has been shown that this approach has the potential to determine the design variables with the highest influence, and therefore, it can reduce the total parameters to a number that is relevant but also manageable for each specific case study [19][20][21][22]. As far as the constraints are concerned, those are usually limited to the critical case-depended features [16,23] or similarly, to common airworthiness aspects like the field performance [13,[24][25][26]. In general, constraints can add further fidelity to the design, and this has been often exemplified through the incorporation of safety regulations in the modeling of fuel systems [27], aircraft controls [28,29], and mission requirements for general aviation [25,30,31].…”
Section: Time Span January Of 2006-december Of 2016 Source Typementioning
confidence: 99%
“…The first and most frequently encountered set of models in MDO of aerial vehicles are the calculation of aerodynamics, the estimation of the weight, the computation of the structural response, and lastly, the assessment of the propulsion specifications. In the conceptual design stage, it is common to use simple and fast aerodynamic predictions which can be provided by empirical equations [24,28] or panel methods [33,34]; however, in cases where more detailed insights into the design are required, it is often shown that computational fluid dynamics (CFD) codes can be a more accurate and hence suitable alternative [35,36]. Similarly, in the initial design phases, the weight and balance are estimated by using empirical equations [24,37] as well as statistical data [38,39], while for additional fidelity, it is also possible to augment the calculations by using the results of simplified [40][41][42] or full [33,43] structural analyses.…”
Section: Disciplinary Modelsmentioning
confidence: 99%